Profile of Students Resilience and Implications of Guidance and Counseling - Pribadi, Pribadi; L.N, Syamsu Yusuf; Yustiana, Yusi Riksa (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2018)
This study aims to obtain a profile of adolescent resilience in grade VIII level of junior high school students. This research uses a descriptive quantitative method. The study was conducted on students of class VIII SMP Negeri 3 Cimahi 2017/2018 academic year with the total population is 452 students, and the number of research samples is 443 students. The instrument used in this study was adapted and modified from the resilience theory in Bonnie Benard's' book "Resiliency: What We Have Learned" and a Likert-scale questionnaire. The results of this research are as follows: 1) The highest aspect is the sense of purpose and bright futures of 83.37%, 2) the lowest issue is the social competence of 68.65%; 3) the highest indicator is spirituality of 91.58%, and 4) the cancel indicator is communication of 60.87%.